TINGKAT KEBUTUHAN MEKANIK PADA SHOWROOM HONDA SOEKARNO HATTA PEKANBARU - Adrian, Nelvo Adrian; Bahar, Aswandi Bahar; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the level of need for Mechanics at Honda Showroom Soekarno Hatta Pekanbaru. This is a descriptive study with a quantitative approach. The population in this study was a mechanic at Honda Showroom Soekarno Hatta Pekanbaru. The samples in this study is the saturated sample. The instrument used in this study was a questionnaire containing 53 items statements, the level of mechanical needs at Honda Showroom Soekarno Hatta Pekanbaru. Alternative answers every item has a statement is very true category is given a score of 4 (four), actually given a score of 3 (three), not really given a score of 2 (two), so not really given a score of 1 (one). From these results it is known that the level of the mechanical requirements on Honda Showroom Soekarno Hatta Pekanbaru included in the high category. This is evidenced from the data summary are: 1. Physiological needs, it is known that 84.11% of respondents answered very true and correct. 2. The need for security, it is known that in this aspect of 85.15% of the respondents answered very true and correct. 3. The need for love and belonging-owned, it is known that 79.27% of respondents who answered very true and correct. 4. The need for an award, it is known that 78.89% of respondents who answered very true and correct answer. 5. The need for self-actualization, it is known that in this aspect as much as 74.59% of respondents who answered very true and correct. This means that the level of the mechanical requirements on Honda Showroom Soekarno Hatta Pekanbaru included in the high category. Keywords: The level of needs, Employees mechanical, Honda Showroom Soekarno Hatta Pekanbaru.